ANALYSIS OF DAIHATSU XENIA'S CAR MARKETING MIX STRATEGY IN INCREASING SALES VOLUME AT PT. KHARISMA SENTOSA IN KENDARI CITY - Hamyat, Hasby; ., Suharlian; Sugandi, Ilham (Sultra Journal of Economic and Business, 2020)
The purpose of this research is to find out whether the marketing strategy is the marketing mix which consists of products, prices, promotions, places, people, processes and physical evidence applied by PT. Kharisma Sentosa Kendari can increase the sales volume of Daihatsu Xenia cars. This research is a qualitative study using a phenomenological approach, data collection using observation interview techniques with samples of employees and customers of PT. Kharisma Sentosa Kendari Branch. The results showed that the marketing strategy adopted by PT. Kharisma Sentosa Kendari in the form of a marketing mix which consists of products, prices, promotion of places, people, processes, and physical evidence has an impact on increasing Daihatsu Xenia's sales. For PT. Kharisma Sentosa Kendari, you should pay more attention to the existing HR resources that are friendly and agile in offering products to customers will provide additional value so that customers are affected to buy Daihatsu Xenia cars at PT. Kharisma Sentosa Kendari Branch.